2016
DOI: 10.1371/journal.pone.0161244
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Oral Health Care to Children under Seven Covered by Bolsa Família Program. Is This a Reality?

Abstract: Over the last decade, there has been a great improvement in the oral health of Brazilians. However, such a trend was not observed among five-year-old children. Dental caries are determined by the interplay between biological and behavioral factors that are shaped by broader socioeconomic determinants. It is well established that dental disease is concentrated in socially disadvantaged populations. To reduce social and health inequalities, the Brazilian government created Family Health Program (ESF), and the Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Further, Oliveira et al (2013) [ 28 ] in a study conducted in the South of Brazil (one of the richest regions of the country) showed that schoolchildren aged 8 to 12 years old who receive BF had worse oral health outcomes than their counterparts. Petrola et al (2016) [ 29 ], who investigated dental care and oral health promotion activities provided by FHT to children and caregivers enrolled in the BFP, identified that most dentists performed no systematic effort to promote oral health care to BFP children, and that, in general, family health professionals did not develop any oral health activities with these children. Nevertheless, the impact of BFP on children’s dental caries remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Oliveira et al (2013) [ 28 ] in a study conducted in the South of Brazil (one of the richest regions of the country) showed that schoolchildren aged 8 to 12 years old who receive BF had worse oral health outcomes than their counterparts. Petrola et al (2016) [ 29 ], who investigated dental care and oral health promotion activities provided by FHT to children and caregivers enrolled in the BFP, identified that most dentists performed no systematic effort to promote oral health care to BFP children, and that, in general, family health professionals did not develop any oral health activities with these children. Nevertheless, the impact of BFP on children’s dental caries remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In an article by Tootooni et al (2015) the prevalence of ECC among children between 2 and 3 years old was reported to be very high, with 61.1% of samples displaying pitted caries [ 7 ]. Despite the improvement in dentistry practice, ECC still remains as remains a serious challenge for health care providers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECC still remains a serious challenge for health care providers, despite the improvement in dentistry practice and decline in the prevalence of dental caries [11]. The prevalence of ECC differs according to the examined groups' age, affected teeth, socioeconomic status, lifestyle, dietary pattern, oral hygiene practices, behavioral factors, race, culture, and ethnicity which differ from country to country [2].…”
Section: Epidemiology Of Eccmentioning
confidence: 99%
“…Johnston T, Messer LB, classified ECC based on the pattern of ECC presentation. Lesions that are associated with developmental defects (pit and fissure defects and hypoplasia) are classified as Type I; smooth surface lesions (labial-lingual lesions, approximal molar lesions) are classified as Type II; rampant caries-having caries in 14 out of 20 primary teeth, including at least one mandibular incisor-are classified as Type III [2,[9][10][11]].…”
mentioning
confidence: 99%